2012
DOI: 10.1007/s10695-012-9745-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Aloe vera components’ effects on cholesterol lowering and estrogenic responses in juvenile goldfish, Carassius auratus

Abstract: Aloes are now considered a very interesting source of bioactive compounds among which phytosterols should play a major role. The present study is an attempt to investigate the hypocholesterolemic activity of Aloe vera associated with its impact on the reproductive status of juvenile goldfish. Therefore, the short- and long-term effects of feeding supplementary diet containing aloe components (20 mg aloe/g diet; 2%) on plasma lipids, plasma vitellogenin, and hepatic estrogen receptor α/β1 mRNA levels in goldfis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…In this study, based on the second-order polynomial regression model analysis, the optimum dietary Aloe inclusion level for HDL activity was determined to be 1.88 %/kg diet. These results partially support the findings of Palermo et al (2013) who reported that 2 % dietary A. vera significantly reduced plasma cholesterol in juvenile goldfish, Carassius auratus, and failed to significantly affect their plasma LDL level. Similarly, a study by Rajasekaran et al (2006) showed that oral administration of A. vera gel extract at a dose of 300 mg/kg body weight per day to streptozotocin-induced diabetic rats significantly reduced plasma and tissue (liver and kidney) TC, TG, and LDL and significantly increased HDL.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, based on the second-order polynomial regression model analysis, the optimum dietary Aloe inclusion level for HDL activity was determined to be 1.88 %/kg diet. These results partially support the findings of Palermo et al (2013) who reported that 2 % dietary A. vera significantly reduced plasma cholesterol in juvenile goldfish, Carassius auratus, and failed to significantly affect their plasma LDL level. Similarly, a study by Rajasekaran et al (2006) showed that oral administration of A. vera gel extract at a dose of 300 mg/kg body weight per day to streptozotocin-induced diabetic rats significantly reduced plasma and tissue (liver and kidney) TC, TG, and LDL and significantly increased HDL.…”
Section: Discussionsupporting
confidence: 90%
“…Some of the microorganisms and oligosaccharides present in the synbiotic preparation may modify blood cholesterol by deconjugating bile acids to produce free bile acids or dropping acetyl Co-A carboxylase (as a limited enzyme in fatty acids synthesis) in the liver and adipose tissue (Ooi & Liong 2010;Velasco et al 2010). The decrease in the serum cholesterol and triglyceride observed in the AV3 group agrees with previous findings in diabetic humans (Choudhary et al 2014) and the juvenile goldfish (Palermo et al 2013). It is suggested that AV can reduce the level of lipids in blood by controlling fat metabolism in the liver (Beppu et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…) and the juvenile goldfish (Palermo et al . ). It is suggested that AV can reduce the level of lipids in blood by controlling fat metabolism in the liver (Beppu et al .…”
Section: Discussionmentioning
confidence: 97%
“…Various species of Aloe genus plants have been proven to exert a diverse range of pharmacological activities. In addition, aloes are now considered to be a very interesting source of bioactive compounds [ 25 ]. Concurrently, some of the pharmacological activities reported, which support the traditional usages of each aloe species, have also been attributed to the presence of a wide range of phytoconstituents.…”
Section: Phytochemical Composition Of Aloe Planmentioning
confidence: 99%